Peran Mahkamah Konstitusi dalam Penyelesaian Sengketa Pemilihan Kepala Daerah - Prio Suryanto Ibrahim; Karmila Saleh; Roy Marthen Moonti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Regional Head Elections (Pilkada) are a manifestation of people's sovereignty and the implementation of democracy in Indonesia, as stipulated in the 1945 Constitution. This study examines the role of the Constitutional Court (MK) in resolving disputes over regional election results. The method used is normative juridical legal research, analyzing relevant regulations and literature. The MK holds permanent authority to adjudicate Pilkada disputes, replacing the Supreme Court. The impact of MK's decisions includes the implementation of Re-voting (PSU), which strengthens the legitimacy of Pilkada results and influences local political stability. However, challenges such as the complexity of evidence and reliance on the MK highlight weaknesses in the oversight system.